A multi-scaled agent-based model of residential segregation applied to a real metropolitan area. (May 2018) - Mahdavi Adrestani, Babak; O'Sullivan, David; Davis, Peter
Abstract: Residential segregation influences many aspects of urban life. It affects people's access to centres of education, healthcare, business and determines the composition of our neighbourhoods, thereby impacting our social network and urban structure. In order to understand the potential impact of policies on residential segregation and complex urban system, a dynamic modelling support tool would be essential. This research article presents a multi-scaled agent-based model capable of simulating the relocation of residents of a representative population of a large urban area in a realistic environment for investigating the dynamics of residential segregation. Using an experiment, we show that this data-driven model can replicate plausible residential distribution and segregation patterns observed in the Auckland region (New Zealand's metropolis). Simulation outcomes are promising, demonstrating the potential of the model for investigating practical policy-relevant questions and acquiring valuable insights into the future state of the urban mosaic landscape and causes behind residential segregation dynamics. Highlights: A multi-scaled agent-based model for investigating the dynamics of residential segregation Model simulates the relocation of residents of a representative population of a large urban area in a realistic environment Simulation experiments performed using Auckland metropolitan area which revealed the following: higher population growth (& immigration) does not necessarily exacerbate the intensity of residential segregation segregation is not necessarily greater at the mesoscale than at the macroscale change of housing vacancy rate has significant impact on the dynamic and intensity of segregation